Quality standards and curriculum for training in cholangiopancreatoscopy: European Society of Gastrointestinal Endoscopy (ESGE) Position Statement - Johnson, Gavin; Webster, George; Papaefthymiou, Apostolis; Teles de Campos, Sara; Czakó, László; Schlag, Christoph; Hollenbach, Marcus; Anderloni, Andrea; Ahmed, Wafaa; Boskoski, Ivo; Ellrichmann, Mark; Gkolfakis, Paraskevas; Hritz, István; Hucl, Tomáš; Kylänpää, Leena; Manno, Mauro; Poley, Jan Werner; Vila, Juan J.; Tham, Tony C.; Ferlitsch, Monika (Endoscopy, 2025)
Quality standards Competence in cholangioscopy should be defined as the ability to successfully perform the procedure effectively, without trainer assistance, in 80 % of procedures. Cholangioscopy should be performed in endoscopy units with a high yearly volume of endoscopic retrograde cholangiopancreatographies (ERCPs) of all grades of complexity. Cholangiopancreatoscopy practice should be considered as standard or advanced as follows: − Standard Cholangioscopy for extrahepatic biliary stones; evaluation of extrahepatic biliary strictures; selective ductal guidewire cannulation and removal of migrated biliary stents/foreign body extraction − Advanced Cholangioscopy for intrahepatic biliary strictures or complex hepatolithiasis; percutaneous cholangioscopy and pancreatoscopy. Endoscopy units undertaking standard cholangioscopy should have prompt access to the following (on site or within a defined rapidly responsive network): − Endoscopic ultrasound (EUS)− Interventional radiology (on-site) and hepaticopancreaticobiliary (HPB) surgery − HPB multidisciplinary meetings (MDMs). Complete extrahepatic stone clearance at the initial cholangioscopy session should be successful in 80 % of intention-to-treat cases. Cholangioscopy is recommended with visually guided biopsies in the evaluation of undefined biliary strictures, ideally at index ERCP to prevent negative visual and histological effects of prior stenting; except in cases with an associated mass lesion that may allow tissue acquisition by other means (e. g. EUS or percutaneous biopsy). In cholangioscopic evaluation of extrahepatic biliary strictures, visual assessment should be achieved in > 90 % of cases, and at least 4 visually guided biopsies should be undertaken with sufficient tissue for histological assessment being obtained in > 80 % of cases. Percutaneous transhepatic cholangioscopy is indicated in patients with transhepatic bile duct access in cases of altered anatomy or failed ERCP and an indication for cholangioscopy (stone management; biliary stricture evaluation; foreign body removal). Curriculum for training Cholangioscopy is considered an advanced adjunct to ERCP, and prior to undertaking supervised cholangioscopic procedures trainees should be competent in the basic skills of ERCP (Schutz level 1 and 2) as defined by ESGE (duodenal intubation; biliary cannulation; distal bile duct stenting; ≤ 10-mm stone extraction). Cholangioscopy training should take place in expert referral centers with a high volume of ERCP and cholangioscopy cases. A trainee’s principal trainer should be an experienced trainer ideally with at least 3 years of experience in undertaking independent cholangioscopy to the determined quality standards. Competence in cholangioscopy should be defined as the ability to successfully perform the procedure effectively without trainer assistance in 80 % of procedures.